Clinical and epidemiological characteristics of a fatal case of avian influenza A H10N8 virus infection: a descriptive study - Chen, HaiYing; Yuan, Hui; Gao, Rongbao; Zhang, Jinxiang; Wang, Dayan; Xiong, Ying; Fan, GuoYin; Yang, Fan; Li, Xiaodan; Zhou, Jianfang; Zou, Shumei; Yang, Lei; et al. (The Lancet (British edition), 2014)
Human infections with different avian influenza viruses—eg, H5N1, H9N2, and H7N9—have raised concerns about pandemic potential worldwide. We report the first human infection with a novel reassortant avian influenza A H10N8 virus. We obtained and analysed clinical, epidemiological, and virological data from a patient from Nanchang City, China. Tracheal aspirate specimens were tested for influenza virus and other possible pathogens by RT-PCR, viral culture, and sequence analyses. A maximum likelihood phylogenetic tree was constructed. A woman aged 73 years presented with fever and was admitted to hospital on Nov 30, 2013. She developed multiple organ failure and died 9 days after illness onset. A novel reassortant avian influenza A H10N8 virus was isolated from the tracheal aspirate specimen obtained from the patient 7 days after onset of illness. Sequence analyses revealed that all the genes of the virus were of avian origin, with six internal genes from avian influenza A H9N2 viruses. The aminoacid motif GlnSerGly at residues 226–228 of the haemagglutinin protein indicated avian-like receptor binding preference. A mixture of glutamic acid and lysine at residue 627 in PB2 protein—which is associated with mammalian adaptation—was detected in the original tracheal aspirate samples. The virus was sensitive to neuraminidase inhibitors. Sputum and blood cultures and deep sequencing analysis indicated no co-infection with bacteria or fungi. Epidemiological investigation established that the patient had visited a live poultry market 4 days before illness onset. The novel reassortant H10N8 virus obtained is distinct from previously reported H10N8 viruses. The virus caused human infection and could have been associated with the death of a patient. Emergency Research Project on human infection with avian influenza H7N9 virus, the National Basic Research Program of China, and the National Mega-projects for Infectious Diseases.